Self-organizing Systems in the Light of the Arrows of Orderedness, Symmetry, and Entropy - György Darvas (tripleC: Communication, Capitalism & Critique)
The paper makes an attempt to resolve two conceptual mingling: (a) the mingling of the two interpretations of the concept of orderedness applied in statistical thermodynamics and in symmetrology, and (b) the mingling of two interpretations of evolution applied in global and local processes. In conclusion, it formulates a new interpretation on the relation of the emergence of new material qualities in selforganizing processes on the one hand, and the evolution of the universe, on the other. The process of evolution is a sequence of emergence of new material qualities by self-organization processes, which happen in negligible small segments of the universe. Although thermodynamics looks at the universe as a closed (isolated) system, this holds for its outside boundaries only, while the universe has many subsystems inside, which are not isolated (closed), since they are in a permanent exchange of matter, energy, etc. with their environment (with the rest of the universe) through their open boundaries. Any ";;emergence";; takes place, i.e., all new qualities come into being just in these small open segments of the universe. The conditions to apply the second law of thermodynamics are not present here. Therefore, global evolution of the universe is the consequence of local symmetry decreases, local decreases of orderedness, and possible local decreases of entropy.